Implementasi Augmented Reality Sebagai Edukasi Pengenalan Wali Songo Dan Sejarahnya Menggunakan Metode Marker Based Tracking Berbasis Android - Ahmad Muhaimin; Ita Handayani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
This study aims to design learning media that are interesting and innovative and able to provide convenience in introducing wali songo to students. The techniques used in collecting data in this study were interviews, observation, and literature study. The tools used to build augmented reality applications include unity, vuforia and blender. In making the design of the assets software used is Adobe Photoshop and using the marker based tracking method. The advantages of the designed application are the application of the marker-based method to the application of learning media with the augmented Reality model, so that it is more interesting and able to increase students' interest in learning. The results of the study are based on the assessment of 34 respondents who were taken from students in the Augmented Reality application of the introduction of Songo Wali to be able to provide interesting and innovative learning media so that it attracts students' interest in learning the history of Songo Wali.